Twenty five years of international exchanges of plant genetic resources facilitated by the CGIAR genebanks: a case study on international interdependence - Galluzzi, Gea; Halewood, Michael; López Noriega, Isabel; Vernooy, Ronnie (Bioversity International, 2015)
This discussion paper, coordinated by Bioversity international and supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is submitted to the Ad Hoc Open-ended Working Group to Enhance the Functioning of the Multilateral System of Access and Benefit-sharing for its consideration.